ANALISIS BUTIR SOAL KONSEP DASAR IPA 1 MELALUI PENGGUNAAN PROGRAM KOMPUTER ANATES VERSI 4.0 FOR WINDOWS - Mahmud Alpusari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2014)
This research was qualitative research with descriptive method. Subject was student teachers who took Fundamental Science 1. Based on validity analysis of item on 1 % significance level, there were 16 valid items, 26 valid ietms for 5 % significance level, and 14 invalid items. Then, analysis of distinguishing items, the item number 20 was very worst, 15 items were poor, other 15 item were fair and the other items were good. Meanwhile, analysis of level of difficulty, 17 item were very easy, 9 items were easy, 11 items were moderate, an item was difficult, and the others were very difficult. Analysis for whole items, there were only 21 items that were ready to be used, 5 items were needed to be revised, and the others could not be used in a testKey words : Konsep Dasar IPA 1, validity, distinguishing items, level of difficulity